2009
DOI: 10.1038/hdy.2009.170
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting relations between diversity of candidate genes and variation of bud burst in natural and segregating populations of European oaks

Abstract: Nucleotide diversity was assessed within nine candidate genes (in total 4.6 kb) for the time of bud burst in nine sessile oak (Quercus petraea) populations distributed in central and northern Europe. The sampled populations were selected on the basis of their contrasting time of bud burst observed in common garden experiments (provenance tests). The candidate genes were selected according to their expression profiles during the transition from quiescent to developing buds and/or their functional role in model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…The highest differentiations were found investigating the genes ALDH, ERD (Part1), and IDH (Part 2) with values above 0.05 (Table 5). Derory et al (2010) found comparable results for SNPs analyzed in candidate genes and microsatellites for Q. petraea.…”
Section: Single Nucleotide Polymorphismssupporting
confidence: 61%
“…The highest differentiations were found investigating the genes ALDH, ERD (Part1), and IDH (Part 2) with values above 0.05 (Table 5). Derory et al (2010) found comparable results for SNPs analyzed in candidate genes and microsatellites for Q. petraea.…”
Section: Single Nucleotide Polymorphismssupporting
confidence: 61%
“…Furthermore, this discrepancy increases as the number of loci involved in the trait increases. (Eveno et al, 2008), bud set in P. sylvestris (Pyhäjärvi et al, 2008) and Picea abies (Heuertz et al, 2006), phenological traits (bud burst, length of growing season and leaf abscission) and growth traits (height growth and diameter) in Populus tremula Luquez et al, 2007), bud burst in Quercus petraea (Derory et al, 2010) and growth, phenology and wood characters in Picea glauca (Namroud et al, 2008). In each case, the level of differentiation of the candidate genes was similar to that of neutral markers, whereas Q ST values were much higher.…”
Section: Discussionmentioning
confidence: 98%
“…A strong expression QTL for ASI was also identified in the same region (Le Provost, unpublished), suggesting that transcript abundance is controlled in cis by polymorphism(s) within or in proximity of the gene, reinforcing its functional, expressional, and positional attributes. The meta-QTL analysis of Derory et al (2010) also showed how repeated phenotypic assessments either among clonal replicates or across years contribute to reduce substantially the confidence intervals of QTLs.…”
Section: Update On Qtl Detectionmentioning
confidence: 99%
“…In Europe, five mapping populations for oak (three Q. robur, one Q. petraea, and one Q. robur × Q. petraea) were produced (https://w3.pierroton.inra.fr/QuercusPortal/index.php). One (Q. robur) has been used to identify genomic regions involved in species differentiation (Scotti-Saintagne et al 2004a), to study the genetic architecture of quantitative traits (Saintagne et al 2004;Scotti-Saintagne et al 2004b;Scotti-Saintagne et al 2005;Gailing et al 2005;Casasoli et al 2006;Parelle et al 2007;Brendel et al 2008;Derory et al 2010), to map genes of interest (Porth et al 2005a) and to examine the level of macrosynteny with European chestnut Casasoli et al 2006) for which one FS mapping population and linkage map was produced.…”
Section: Available Mapping Populations In the Fagaceaementioning
confidence: 99%
See 1 more Smart Citation